Perancangan Logo dan Standar Manual Grafis untuk Membangun Citra Identitas Badan Usaha Milik Desa Sukses Bersama Simpang - Dafy Cahya Nugroho; Alfian Candra Ayuswantana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
A logo is a medium for communicating values, goals, and creating an impression of professionalism from an institution. Meanwhile, standard logo graphic manuals are a medium for communicating values, goals, and creating an impression of professionalism from an institution. These two elements are interrelated and inseparable. This journal discusses visual identity design, especially logos and graphic manual standards for the Sukses Bersama Simpang Village-Owned Enterprise which is implemented in the Merdeka College Competency Program (PKKM). Village Development Students at the East Java